Socioemotional Education to Decrease Attitudes of School Violence - Calle Romero, Hermelinda de Jesus (2024)
The research was carried out with the purpose of demonstrating that the implementation of the Socio-emotional Education Program contributes to reducing attitudes of School Violence in Superior Basic students at an Educational Institution in Ecuador during the year 2023. To achieve this objective, an applied methodology was adopted with a quantitative approach and a quasi-experimental design. The sample consisted of 76 students, evenly divided into a control group and an experimental group, to whom a pretest and a posttest of the school violence questionnaire were administered. The pretest results revealed that 27.6% (16 participants) of the control group and 40.8% (31 participants) of the experimental group had a high attitude towards school violence. In the posttest, the control group recorded a 25% high attitude, while the experimental group, after the implementation of the socio-emotional education program, evidenced that 42.1% showed a low attitude towards school violence. The analysis of significant differences yielded a p-value of 0.00, less than 0.05. These numerical results support the importance of the specific interventions of the implemented program, as they generate significant changes in student attitudes, promoting positive school coexistence.